GABAA Receptors Are Involved in the Seizure Blockage Prompted by a Polyphenol-Rich Extract of White Grape Juice in Rodents - Alessandro Maugeri; Rita Citraro; Antonio Leo; Caterina Russo; Michele Navarra; Giovambattista De Sarro (Pharmaceuticals)
Background/Objectives: Polyphenols have been suggested to possess anticonvulsant properties, which can be exploited as tools in novel strategies against epilepsy. Along that line, the aim of this study was to investigate the effects of a polyphenol-rich extract of white grape juice (WGJe) in different rodent models of epilepsy, exploring its putative mechanism of action. Methods: In this study, we employed pentylenetetrazole (PTZ)-injected ICR-CD1 mice, audiogenic seizure (AGS)-susceptible DBA/2 mice and WAG/Rij rats. Seizures were monitored and scored, while absence was assessed by electroencephalogram. The open-field test was employed to assess the anxiolytic effects of WGJe. In order to assess the involvement of the GABAA receptor, we used the antagonist flumazenil in AGS-susceptible DBA/2 mice. Computational analyses were employed to evaluate the interaction of the main polyphenols of WGJe and GABAA receptors. Results: Our results showed that the intraperitoneal injection of WGJe hindered tonic seizures in PTZ-injected ICR-CD1 mice. In WAG/Rij rats, WGJe did not elicit any significant effects on spike-wave discharges compared to untreated rats. In AGS-susceptible DBA/2 mice, WGJe significantly hampered both clonic and tonic seizures, as well as induced anxiolytic effects. Interestingly, when administering WGJe with flumazenil to DBA/2 mice, we noted that the observed effects were mediated by the GABAA receptor. Moreover, docking simulations confirmed that the main polyphenols of WGJe are able to interact with the benzodiazepine sites located in both extracellular and transmembrane domains in the GABAA receptor. Conclusions: This study outlines the mechanism underlying the anti-epileptic activity of WGJe, thus supporting its potential role in the management of epilepsy.